Impact of Temperature and Irradiance on PV Array Performance and Withstand Voltage - Jia Wen Tang; Chin Leong Wooi; Wen Shan Tan; Nur Hazirah Zaini; Yuan Kang Wu; Syahrun Nizam bin Md Arshad@Hashim (Iranian Journal of Electrical and Electronic Engineering)
Photovoltaic (PV) energy is increasingly recognized as an environmentally friendly source of renewable energy. Integrating PV systems into power grids involves power electronic inverters, adding complexity and evolving traditional grids into smarter systems. Ensuring the reliability of decentralized PV generation is crucial, particularly as PV systems are often exposed to extreme weather conditions. This study investigates the impact of temperature and solar radiation on the performance of a PV array, focusing on key characteristics such as open-circuit voltage (VOC), short-circuit current (ISC), and maximum power (PMAX). Using PSCAD/EMTDC simulations, the study analyses these characteristics under varying temperatures (5°C to 45°C) and radiation levels (200 W/m² to 1200 W/m²). Results indicate that VOC increases with higher irradiance but decreases with higher temperatures. ISC increases with both higher radiation and temperature, while PMAX is optimized at high irradiance and low temperatures. The impulse withstand voltage (Vimp), a critical factor for PV system reliability, is assessed according to the PD CLC/TS 50539-12 standard. Findings reveal that at low temperatures and high radiation, the Vimp requirement is highest, emphasizing the need for robust voltage protection in PV systems. These insights underscore the importance of considering local climate conditions and implementing effective thermal management to enhance the performance and reliability of PV systems.